Functional advantage of educated KIR2DL1+ natural killer cells for anti‐HIV‐1 antibody‐dependent activation. (4th February 2016) - Gooneratne, S. L.; Center, R. J.; Kent, S. J.; Parsons, M. S.
Summary: Evidence from the RV144 HIV‐1 vaccine trial implicates anti‐HIV‐1 antibody‐dependent cellular cytotoxicity (ADCC) in vaccine‐conferred protection from infection. Among effector cells that mediate ADCC are natural killer (NK) cells. The ability of NK cells to be activated in an antibody‐dependent manner is reliant upon several factors. In general, NK cell‐mediated antibody‐dependent activation is most robust in terminally differentiated CD57 + NK cells, as well as NK cells educated through ontological interactions between inhibitory killer immunoglobulin‐like receptors (KIR) and their major histocompatibility complex class I [MHC‐I or human leucocyte antigen (HLA‐I)] ligands. With regard to anti‐HIV‐1 antibody‐dependent NK cell activation, previous research has demonstrated that the epidemiologically relevant KIR3DL1/HLA‐Bw4 receptor/ligand combination confers enhanced activation potential. In the present study we assessed the ability of the KIR2DL1/HLA–C2 receptor/ligand combination to confer enhanced activation upon direct stimulation with HLA‐I‐devoid target cells or antibody‐dependent stimulation with HIV‐1 gp140‐pulsed CEM.NKr‐CCR5 target cells in the presence of an anti‐HIV‐1 antibody source. Among donors carrying the HLA‐C2 ligand for KIR2DL1, higher interferon (IFN)‐γ production was observed within KIR2DL1 + NK cells than in KIR2DL1 – NK cells upon both direct and antibody‐dependent stimulation. No differences in KIR2DL1 + and KIR2DL1 – NK cell activation were observed in HLA‐C1 homozygous donors. Additionally, higher activation in KIR2DL1 + than KIR2DL1 – NK cells from HLA–C2 carrying donors was observed within less differentiated CD57 – NK cells, demonstrating that the observed differences were due to education and not an overabundance of KIR2DL1 + NK cells within differentiated CD57 + NK cells. These observations are relevant for understanding the regulation of anti‐HIV‐1 antibody‐dependent NK cell responses.